Contemporary Ukrainian cinema into the European context (2014-2019) - Alforova, Zoya; Marchenko, Serhii; Shevchuk, Yuliia; Kotlyar, Svitlana; Honcharuk, Serhii (Linguistics and Culture Review, 2021)
The relevance of the study is conditioned by the fact that the development of Ukrainian art, including cinema, is becoming more popular every year. Since 2014, the Ukrainian film industry has been rapidly developing, and has also shown good results at European and other international film festivals. The purpose of the study is to analyse the position of Ukrainian cinema in the recent historical period, as well as to analyse the preconditions that were created for its development and introduction to the European cinema market. The methodological basis of this study is the combination of theoretical methods of cognition. Methods of data analysis and synthesis, dialectical method, historical and periodisation method are used. In the course of writing this paper, the studies of Ukrainian and foreign researchers regarding the subject were studied and analysed. The establishment and current state of the film industry are investigated. The preconditions for the development of Ukrainian cinema as well as factors that influenced its entrance to the European market are considered. Studying the history of Ukrainian cinema and the process of its commercial distribution, will help to analyse the stages of its establishment, as well as explore opportunities for industry development.